Comorbidity and long‐term clinical outcome of laryngotracheal clefts types III and IV: Systematic analysis of new cases. Issue 1 (5th November 2020) - Seidl, Elias; Kramer, Johanna; Hoffmann, Florian; Schön, Carola; Griese, Matthias; Kappler, Matthias; Lisec, Kristina; Hubertus, Jochen; von Schweinitz, Dietrich; Di Dio, Diana; Sittel, Christian; Reiter, Karl
Abstract: Background: Long segment laryngotracheoesophageal clefts (LTECs) are very rare large‐airway malformations. Over the last 40 years mortality rates declined substantially due to improved intensive care and surgical procedures. Nevertheless, long‐term morbidity, comorbidity, and clinical outcomes have rarely been assessed systematically. Methods: In this retrospective case series, the clinical presentation, comorbidities, treatment, and clinical outcomes of all children with long‐segment LTEC that were seen at our department in the last 15 years were collected and analyzed systematically. Results: Nine children were diagnosed with long segment LTEC (four children with LTEC type III and five patients with LTEC type IV). All children had additional tracheobronchial, gastrointestinal, or cardiac malformations. Tracheostomy for long‐time ventilation and jejunostomy for adequate nutrition was necessary in all cases. During follow‐up one child died from multiorgan failure due to sepsis at the age of 43 days. The clinical course of the other eight children (median follow‐up time 5.2 years) was stable. Relapses of the cleft, recurrent aspirations, and respiratory tract infections led to repeated hospital admissions. Conclusions: Long‐segment LTECs are consistently associated with additional malformations, which substantially influence long‐term morbidity. For optimal management, a multidisciplinary approach is essential.